2012
DOI: 10.1002/app.38782
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured thermosetting epoxy systems modified with poly(isoprene‐b‐methyl metacrylate) diblock copolymer and polyisoprene‐grafted carbon nanotubes

Abstract: Nanostructured thermosetting composites based on an epoxy matrix modified with poly(isoprene‐b‐methyl methacrylate) (PI‐b‐PMMA) block copolymer were prepared through PI block segregation. Morphological structures were examined by means of atomic microscopy force microscopy. As epoxy/pristine multi‐walled carbon nanotubes (MWCNT) systems were found to present big agglomerations, with a very poor dispersion of the nanofiller, epoxy/PI‐b‐PMMA/MWCNT systems were prepared by using polyisoprene‐grafted carbon nanotu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 30 publications
0
1
1
Order By: Relevance
“…But some studies have focused on the analysis of mechanical properties of simultaneous addition of MWCNT and TBCP without any chemical modification. But the results were not promising as toughness improvements were obtained at higher filler loadings with the loss of tensile strength. But in the current study, it is found that with a lower loading (i.e 0.1 wt %) of the graft a toughness improvement of about 367% is obtained without affecting the tensile property as shown in Figure . Table compares the toughness obtained for the current system with the previous studies.…”
Section: Resultscontrasting
confidence: 61%
“…But some studies have focused on the analysis of mechanical properties of simultaneous addition of MWCNT and TBCP without any chemical modification. But the results were not promising as toughness improvements were obtained at higher filler loadings with the loss of tensile strength. But in the current study, it is found that with a lower loading (i.e 0.1 wt %) of the graft a toughness improvement of about 367% is obtained without affecting the tensile property as shown in Figure . Table compares the toughness obtained for the current system with the previous studies.…”
Section: Resultscontrasting
confidence: 61%
“…More recently, the formation of CNT–BCP patchy conjugates by noncovalent functionalization of CNT with polystyrene- b -polyethylene- b -poly­(methyl methacrylate) triblock copolymer was described, and their potential use as reinforcements in polymer blend nanocomposites was suggested . However, articles investigating material properties of epoxy thermosets modified with CNT and BCP are scarce, and significant improvements on material properties are yet to be achieved. For instance, Martin-Gallego et al reported an increment of ∼15% in the critical stress intensity factor with respect to neat epoxy for an epoxy nanocomposite bearing multiwalled carbon nanotubes (0.25 wt %) and poly­(ethylene oxide)–poly­(propylene oxide)–poly­(ethylene oxide) BCP (10 wt %), while the addition of CNT (0.25 wt %) or BCP (10 wt %) led to increments of ∼13% with the same property compared to neat epoxy.…”
Section: Introductionmentioning
confidence: 99%